2020
DOI: 10.1371/journal.pgen.1008724
|View full text |Cite
|
Sign up to set email alerts
|

Integrative and quantitative view of the CtrA regulatory network in a stalked budding bacterium

Abstract: The Alphaproteobacteria show a remarkable diversity of cell cycle-dependent developmental patterns, which are governed by the conserved CtrA pathway. Its central component CtrA is a DNA-binding response regulator that is controlled by a complex two-component signaling network, mediating distinct transcriptional programs in the two offspring. The CtrA pathway has been studied intensively and was shown to consist of an upstream part that reads out the developmental state of the cell and a downstream part that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Construction of ctrA knockout mutants failed or they showed severe growth defects in the Caulobacterales C. crescentus ( Quon et al, 1996 ; Christen et al, 2011 ; Guzzo et al, 2020 ) and Hyphomonas neptunium ( Leicht et al, 2020 ) as well as the Rhizobiales Sinorhizobium meliloti ( Barnett et al, 2001 ) and Brucella abortus ( Bellefontaine et al, 2002 ), but has no negative effects on growth or viability in the Sphingomonadales Sphingomonas melonis ( Francez-Charlot et al, 2015 ), Rhodospirillales Rhodospirillum centenum ( Bird and MacKrell, 2011 ) and Magnetospirillum magneticum ( Greene et al, 2012 ), as well as the Rhodobacterales members studied so far ( Miller and Belas, 2006 ; Mercer et al, 2010 ; Zan et al, 2013 ; Wang et al, 2014 ; Hernández-Valle et al, 2020 ). While the influence of CtrA on replication has been demonstrated in Sphingomonas melonis and some Rhodobacterales, these bacteria lack a strict dimorphic lifestyle or polar growth that has been demonstrated for the Caulobacterales and Rhizobiales.…”
Section: Ctra and Cell Cycle Control In Alphaproteobacteriamentioning
confidence: 99%
“…Construction of ctrA knockout mutants failed or they showed severe growth defects in the Caulobacterales C. crescentus ( Quon et al, 1996 ; Christen et al, 2011 ; Guzzo et al, 2020 ) and Hyphomonas neptunium ( Leicht et al, 2020 ) as well as the Rhizobiales Sinorhizobium meliloti ( Barnett et al, 2001 ) and Brucella abortus ( Bellefontaine et al, 2002 ), but has no negative effects on growth or viability in the Sphingomonadales Sphingomonas melonis ( Francez-Charlot et al, 2015 ), Rhodospirillales Rhodospirillum centenum ( Bird and MacKrell, 2011 ) and Magnetospirillum magneticum ( Greene et al, 2012 ), as well as the Rhodobacterales members studied so far ( Miller and Belas, 2006 ; Mercer et al, 2010 ; Zan et al, 2013 ; Wang et al, 2014 ; Hernández-Valle et al, 2020 ). While the influence of CtrA on replication has been demonstrated in Sphingomonas melonis and some Rhodobacterales, these bacteria lack a strict dimorphic lifestyle or polar growth that has been demonstrated for the Caulobacterales and Rhizobiales.…”
Section: Ctra and Cell Cycle Control In Alphaproteobacteriamentioning
confidence: 99%
“…A recent publication has shed light on the CtrA pathway in H. neptunium and shown that it is also critical for cell cycle regulation in stalked budding bacteria (Leicht et al 2020). In vitro experiments confirmed that the (de)phosphorylation of CtrA through the CckA-ChpT phosphorelay and of DivK through DivJ and PleC is conserved in this species.…”
Section: Ctra-dependent Cell Cycle Regulation In Stalked Budding Bactmentioning
confidence: 68%
“…In this respect, it is interesting to note that H. neptunium cells can tolerate the loss of PopZ without showing any obvious phenotype (Jung et al 2019), which raises the question whether polar microdomains play a significant role in cell cycle regulation in this species. Another striking difference that might reflect a difference in the regulation of CckA is the lack of a phenotype for the loss of PleD, which could indicate that c-di-GMP may have no (major) role in CckA regulation (Leicht et al 2020). A notable difference is finally also seen in the mechanisms that control CtrA stability.…”
Section: Ctra-dependent Cell Cycle Regulation In Stalked Budding Bactmentioning
confidence: 99%
“…The 1D and 2D demo‐ and kymographs, the use of concatenated intensity profiles, the possibility to align these profiles based on the morphologically relevant criteria (e.g., alignment at the junction between the mother cell and stalk, or flagellum, or at a specific pole), and the option to display specific subsets of cells (i.e., swarmer cells, stalked cells without buds, and budding cells) are instrumental in understanding the localization behavior of proteins in different cell types in a mixed population. This is exemplified by an analysis of the localization dynamics of the histidine kinase CckA in H. neptunium using BacStalk, which verified the cell cycle‐dependent localization previously observed in a qualitative manner (Leicht et al ., 2020). BacStalk provides a means to automatically plot the intracellular localization of CckA‐Venus in demographs separately for swarmer cells, stalked cells without buds, and budding cells (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%